Edukasi Literasi Keuangan Digital Berbasis Smartphone Bagi Mahasiswa dalam Menghadapi Tantangan Ekonomi Digital - Dwi Utami; Sri Utami; Desi Ratna Dewi; Patahuddin (Publikasi Inspirasi Indonesia, 2026)
The rapid growth of the digital economy has increased the use of digital financial services among university students. However, the extensive utilization of financial technology has not been fully supported by adequate digital financial literacy skills. This condition exposes students to various risks, including consumptive behavior, digital fraud, misuse of personal data, and poor financial decision-making. This Community Service Program aimed to enhance students’ understanding and skills in managing digital finance through smartphone-based digital financial literacy education. The program employed interactive lectures, discussions, simulations of digital financial applications, and evaluations using pre-tests and post-tests. Students actively participated in all stages of the program. The results indicated an improvement in students’ understanding of digital financial literacy concepts, digital transaction security, personal financial management, and the responsible use of digital financial services. In addition, participants demonstrated increased awareness of the importance of protecting personal data, avoiding digital fraud, and controlling consumptive behavior in financial technology usage. Smartphone-based digital financial literacy education proved to be an effective approach for improving students’ ability to face the challenges of the digital economy. Similar programs should be implemented continuously to strengthen digital financial literacy among young generations in the era of digital transformation.